2011
DOI: 10.4081/nursrep.2011.e2
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards older people among Swedish health care students and health care professionals working in elder care

Abstract: The proportion of older people in the general population has increased and will continue to increase during the coming decade. Therefore, a positive attitude towards older people is important. The aim of the study was to gain knowledge about attitudes towards older people among health care students and health care staff in Swedish elder care settings. The study includes a convenience sample of 928 respondents comprised of health care students and three groups of professional caregivers [registered nurses (RNs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
3
26
0
1
Order By: Relevance
“…The Swedish students' age was positively associated with their positive attitudes; with age, the students developed higher positive scores. These results confirm those of other Swedish researchers (Engström & Fagerberg, 2011;Söderhamn et al, 2001) who demonstrate that the age of respondents relates to positive attitudes toward older persons. However, Lee (2009) did not find that older students had better attitudes toward aging, which might be due to the small sample of older students in the study.…”
Section: Discussionsupporting
confidence: 95%
“…The Swedish students' age was positively associated with their positive attitudes; with age, the students developed higher positive scores. These results confirm those of other Swedish researchers (Engström & Fagerberg, 2011;Söderhamn et al, 2001) who demonstrate that the age of respondents relates to positive attitudes toward older persons. However, Lee (2009) did not find that older students had better attitudes toward aging, which might be due to the small sample of older students in the study.…”
Section: Discussionsupporting
confidence: 95%
“…All selected studies reported an association between advanced education levels and positive attitudes 3,8,14-17,21-25,27. Adibelli and Kilic’s23 study indicated that positive attitudes toward older people increased with higher levels of education that include university degree and postgraduate degree.…”
Section: Factors Affecting Knowledge and Attitudes Toward Older Peoplementioning
confidence: 99%
“…The AAS measures social beliefs and perceptions about the social life of older people as well as social opinions and views toward older people 16. The AAS contains 23 statements, which are rated on a 5-point Likert scale 14. Finally, the Chinese version of the Ageing Semantic Differential (CASD) is a 32-item scale, which is widely used to assess attitudes toward older people 17.…”
Section: Instruments Used To Measure Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…An awareness about the normality in aging, knowledge of natural aging processes as well as what is culturally important and relevant in service delivery, which has been acknowledged by Elliot (2005), may help change negative attitudes towards working within elder care (Engström & Fagerberg, 2011;McCann et al, 2010). The demand for education in gerontology and geriatrics is now also emerging from research within Australasia and Africa (Cheng et al, 2015a;Fajemilehin, 2004;Henderson et al, 2008;Hirst & Cole, 2014;Kumar et al, 2012;Liu et al, 2013), stressing that the amount of education in these areas will have an impact on the students' understanding of the needs of elderly patients (Fagerberg & Gilje, 2007).…”
Section: Discussionmentioning
confidence: 99%